Relación que se establece entre la comunidad de Viñales y el Parque Nacional Viñales - Martín Hernández, J.; Valdivia, M. A.; Domínguez, M. (Geographicalia, 2016)
Faced with the presence of population within or near the Protected Areas, the assimilation of the nature protection process becomes necessary in these communities, as a basic principle  to achieve a sustainable use of the natural resources. That is why the main objective of this work was to determine the relations that are established between the community of Viñales and the Viñales National Park. After discovering these relations and the opinions of the inhabitants of the community about the park, a plan of action was created to educate the inhabitants and make them environmentally aware, in order to achieve its protection
Keywords: Protected areas; communities; natural park; environmental education.